Division of labor in Ectatomma edentatum (Hymenoptera, Formicidae) - Antonialli-Junior, William Fernando [UNESP]; Giannotti, Edilberto [UNESP] (My University, 2002)
The behavioral division of labor between queens and workers of E. edentatum was investigated under laboratory conditions. Each behavioral category of both castes was described by direct observation of the ants in the colonies. The spatial position and the behavior of each individual were recorded. A colony ethogram was constructed to determine comparatively the behavioral repertory of the 2 castes. Most of the members of the colonies, including the queens, occupied the 2nd chamber, which also contained the immature stages. Forty-two behavioral categories were recorded for the workers, and 28 for the queens. The comparison of the behavioral repertory of the 2 castes revealed that ovipositing a fecundated egg is an exclusive behavior of the queens, while the workers showed 15 exclusive behaviors. Queens were never seen foraging out of the nest. Twelve behaviors were common for both castes. Polygynic colonies have only 1 female with full-developed ovaries, which is the main egg layer of the group, a feature defining the social organization of colonies of E. edentatum as a functional monogyny.
Keywords: Ectatomma edentatum; Formicidae; Hymenoptera